Correlation between Fine-Needle Aspiration Cytology and Histology for Palpable Breast Masses in a Nigerian Tertiary Health Institution - Adetola Olubunmi Daramola; Mosebolatan Olatokunboh Odubanjo; Fred John Obiajulu; Nzechukwu Zimudo Ikeri; Adekunbiola Aina Fehintola Banjo (International Journal of Breast Cancer)
Background. Management of breast lumps can be challenging in resource poor settings. Fine-needle aspiration cytology (FNAC) especially when used with cell block can help improve affordability for the patients. Objective. To determine the diagnostic accuracy of FNAC of palpable breast lesions within a 5-year period. Methods. The findings obtained from FNAC of palpable breast lumps seen at the FNAC clinic of our department from January 2007 to December 2011 were retrieved and correlated with findings on histology of excisional biopsies. Results. A total of 1790 patients had FNAC of breast lumps during the 5-year period; 436 of them subsequently had biopsies. Our results compare favourably with the measures of test performance of the UK NHS Breast Screening Programme shown in brackets: absolute sensitivity 95.4% (>70%), complete sensitivity 99.2% (>90%), full specificity 88.9% (>65%), positive predictive value 99.6% (>99%), false-negative rate 0.8% (<4%), false-positive rate 0.4% (<0.5%), inadequate rate 3.2% (<15%), and suspicious rate 10.2% (<15%). Conclusion. Breast FNACs compare very well with histology of excisional biopsies and in experienced hands are extremely useful in the management of breast lumps. Further studies assessing the diagnostic accuracy of FNAC and cell blocks in our setting are recommended.